2023
DOI: 10.1038/s41598-023-31902-3
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in time to first antenatal care visits and its predictors among pregnant women in India: an evidence from national family health survey

Abstract: For countries with high maternal mortality and morbidity, on-time initiation of antenatal care (ANC) is indispensable. Therefore this paper aims for studying the median survival time (MST) of first ANC among pregnant women as well as understanding the contextual factors that influence a mother’s decision to access ANC services in India. The study used cross-sectional survey data obtained from the NFHS-4 conducted in 2015–2016. The MST of the timing of the first ANC visit was estimated using the Kaplan-Meir est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
2

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
3
14
2
Order By: Relevance
“…The current study revealed that mothers who belong to the poorest and poorer socioeconomic statuses were 90% more likely to delay their ANC initiation compared to those with the richest socioeconomic status. This finding supports the results of studies conducted in Ethiopia [ 22 ], Ghana [ 33 ], and India [ 41 , 42 ]. This might be due to the out-of-pocket expenditure associated with the service.…”
Section: Discussionsupporting
confidence: 91%
“…The current study revealed that mothers who belong to the poorest and poorer socioeconomic statuses were 90% more likely to delay their ANC initiation compared to those with the richest socioeconomic status. This finding supports the results of studies conducted in Ethiopia [ 22 ], Ghana [ 33 ], and India [ 41 , 42 ]. This might be due to the out-of-pocket expenditure associated with the service.…”
Section: Discussionsupporting
confidence: 91%
“…The mean survival time of pregnant women to initiate ANC visits in this study was significantly higher than a study done in India in which the reported median survival time to the first ANC visit was 4 months. 33 The finding of this study is also slightly higher than the study finding from Nigeria in which the median survival time for the first ANC check-up was found to be 6 months. 34 Moreover, this finding is higher when compared with the recent findings of average of 3.4 gestational months before initiation of ANC visits in Ghana.…”
Section: Discussioncontrasting
confidence: 73%
“… 11 33 39 A study conducted in India revealed that women with higher education had a 2.8 times shorter time to initiate ANC in the first trimester of pregnancy compared with women having no formal education. 33 Similarly, in Nepal, women with higher-level education were significantly more likely to initiate ANC early compared with women who had no education. 39 A multicountry analysis of DHS in SSA found that the odds of timely initiation of ANC were higher in mothers who had a higher level of education compared with women who had no formal education.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations